Aerosol and cloud radiative forcing over various hot spot regions in India. Issue 8 (15th October 2019) - Sivan, C.; Manoj, M.G.
Highlights: Spatio-temporal distribution of aerosol and cloud radiative forcings over India. Three hot spot regions show higher aerosol loading. Maximum aerosol forcing and heating rate in pre-monsoon season. Enhanced cloud forcing in monsoon season. Abstract: Twelve years of NASA CERES (Clouds and Earth's Radiant Energy System) data have been used to examine the spatio-temporal variability of aerosol– and cloud– induced shortwave radiative forcing over selected hot spot regions in India. Four regions (northern semiarid – R1; monsoon trough – R2; densely populated urban – R3; and southern peninsula – R4) are selected with different surface characteristics and notable difference in meteorological and geographical features. The analysis shows that three out of the four regions (viz. R1, R2, and R3) experience high aerosol loading and forcing in the monsoon season followed by moderate forcing in pre-monsoon season. While all the seasons except the post-monsoon period show a positive linear relation between cloud optical depth and aerosol optical depth for all the regions, the post-monsoon season shows a negative relation. However, the relation between aerosol forcing and cloud forcing shows adequate non-linearity owing to the numerous factors that control cloud radiative effect. The estimated aerosol induced heating rate shows exponential decrease with height, but with high variability during each season. Irrespective of any region, the maximum heating rate is observed in the pre-monsoon season (2.86 ± 0.78, 2.49 ± 0.78, 1.89 ± 0.57, and 0.88 ± 0.28 K/day for R1, R2, R3, and R4, respectively). Plausible reasons for the variation in the above parameters are discussed. The results suggest that increased anthropogenic activities affect the thermodynamics and hence the dynamics through retention and exchange of heat, and it could affect the precipitation pattern adversely.